2011
DOI: 10.1088/0953-4075/44/5/055201
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical confirmation of the role of higher order mechanisms in the electron impact double ionization of helium

Abstract: Our recent measurements (Lahmam-Bennani et al 2010 J. Phys. B: At. Mol. Opt. Phys. 43 105201) of the (e,3-1e) four-fold differential cross sections (4DCS) for double ionization (DI) of helium are extended here to a wider range of ejected electron energies and very asymmetric energy sharing. Previous observations of large angular shifts in the experimental 4DCS distributions with respect to the momentum transfer axis are once again reproduced by the new measured data. Moreover, a comparison of all the data sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…Let us also cite the more recent experiment of Li et al [23] where double ionization of neon, argon, and molecular nitrogen targets impacted by 600-to 700-eV electron beams was investigated. Thus, the fourfold differential cross sections obtained have demonstrated that the double ionization of small atoms or molecules was dominated-at least within the energy range studied (600-700 eV)-by non-first-order mechanisms such as the two-step (TS2) one, as previously shown by Staicu Casagrande et al [24] for helium. Regarding the double ionization of oriented molecules, there are, to the best of our knowledge, only a few cases reported in the literature.…”
Section: Introductionsupporting
confidence: 78%
“…Let us also cite the more recent experiment of Li et al [23] where double ionization of neon, argon, and molecular nitrogen targets impacted by 600-to 700-eV electron beams was investigated. Thus, the fourfold differential cross sections obtained have demonstrated that the double ionization of small atoms or molecules was dominated-at least within the energy range studied (600-700 eV)-by non-first-order mechanisms such as the two-step (TS2) one, as previously shown by Staicu Casagrande et al [24] for helium. Regarding the double ionization of oriented molecules, there are, to the best of our knowledge, only a few cases reported in the literature.…”
Section: Introductionsupporting
confidence: 78%
“…The B2-2CG results are shown as full curves in Fig. 1 A strong disagreement is found between first Born calculations and experiments for Ne and Ar, the disagreement being appreciably more pronounced than was observed previously for He [1,2]. Indeed, for both atomic targets the B1-3C and B1-2CG models yield forward and backward angular distributions which are symmetrically distributed about ±K directions, as it is expected from any first-order theory, whereas the experiments do not show such symmetry.…”
Section: Resultsmentioning
confidence: 75%
“…The experimental set-up and procedure used in the present work are identical to those used in [1,2] and are described in detail in [10]. Briefly, a well-collimated electron beam with energy E 0~6 00 -700 eV (see below) ionises a gas jet formed at the collision centre by the effusive flow of gas through a small capillary.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both mechanisms have been investigated in a number of recent works (e.g. [4][5][6][7]), but on a quantitative level the question concerning their relative importance and thus of the role of correlation in DI remains to a large extent open.…”
mentioning
confidence: 99%